2019
DOI: 10.1128/mcb.00428-18
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Mpo1 Is a Novel Dioxygenase That Catalyzes the α-Oxidation of a 2-Hydroxy Fatty Acid in an Fe2+-Dependent Manner

Abstract: Phytosphingosine (PHS) is the major long-chain base component of sphingolipids in Saccharomyces cerevisiae. The PHS metabolic pathway includes a fatty acid (FA) α-oxidation reaction. Recently, we identified the novel protein Mpo1, which is involved in PHS metabolism. However, the details of the FA α-oxidation reaction and the role of Mpo1 in PHS metabolism remained unclear. In the present study, we revealed that Mpo1 is involved in the α-oxidation of 2-hydroxy (2-OH) palmitic acid (C16:0-COOH) in the PHS metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Therefore, iron depletion alters the sphingolipid synthesis pathway [20]. Moreover, a recent report has shown that Mpo1 is a novel iron-dependent dioxygenase involved in phytosphingosine metabolism [49,50]. Various studies suggest that sphingolipid metabolism could also modulate Aft1 function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, iron depletion alters the sphingolipid synthesis pathway [20]. Moreover, a recent report has shown that Mpo1 is a novel iron-dependent dioxygenase involved in phytosphingosine metabolism [49,50]. Various studies suggest that sphingolipid metabolism could also modulate Aft1 function.…”
Section: Discussionmentioning
confidence: 99%
“…The -oxidation reactions differ between mammals and yeast. Mammalian -oxidation involves three steps (CoA addition, long-chain aldehyde production by cleavage between the C1 and C2 positions, and oxidation to FAs), whereas yeast -oxidation is conducted in one step (17,18,24). Accordingly, the proteins involved in -oxidation differ between mammals and yeast.…”
Section: Enzymatic Characterization Of Mpo1 1105mentioning
confidence: 99%
“…We previously identified MPO1 as the gene functioning in the degradation pathway of PHS in yeast (17). It subsequently became clear that Mpo1 is involved in the oxidation of 2-OH FAs as an Fe 2+ -dependent dioxygenase (EC 1.14.18.12), which directly converts 2-OH LCFAs to nonhydroxy FAs with one less carbon (24).…”
Section: Enzymatic Characterization Of Mpo1 1105mentioning
confidence: 99%
See 1 more Smart Citation
“…Mpo1 is an Fe II -containing dioxygenase in the ER membrane that catalyzes the oxidation of a 2-hydroxy fatty acid. 190 Unlike the other biosynthetic enzymes just discussed, Mpo1 helps degrade a membrane component rather than synthesize one.…”
Section: Endoplasmic Reticulum (Er)mentioning
confidence: 99%